A new record of a mealybug species (Hemiptera: Coccoidea: Pseudococcidae) from Tristan da Cunha and a new description of the species (Bollettino di zoologia agraria e bachicoltura, 2024)
The rhizoecine mealybug Rhizoecus bolacis Williams is here recorded from Tristan da Cunha, bringing the total number of scale insect species known from this archipelago to two! The adult female is redescribed and what is probably the 2nd-instar female is described. The generic placement of this species is discussed.
Keywords: cocciniglia ipogea; Rhizoecinae; Rhizoecus bolacis